2015
DOI: 10.1163/15685411-00002928
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of three families of the suborder Mononchina Kirjanova & Krall, 1969 inferred from 18S rDNA

Abstract: Mononchida is an order of predatory nematodes and includes the suborders Bathyodontina and Mononchina. In this survey, sequences of the 18S rDNA were amplified and used to reconstruct the phylogeny of the Mononchina. Phylogenetic analyses using Neighbour Joining (NJ) and Maximum Likelihood (ML) were employed with five outgroup taxa and 65 mononch sequences including 14 new sequences from Iran. Both analyses indicated that the Anatonchus is monophyletic. Actus was placed as the sister group of Mylonchulus with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…The present results indicate that 18S rDNA sequence data are a valuable marker for the phylogenetic analysis within Mylonchulus species. This agrees with the previous result obtained [5,11,35]. Tree topology using Bayesian inference shows that M. hawaiiensis stand separately, which contrasts with the result obtained by Olia et al [35].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The present results indicate that 18S rDNA sequence data are a valuable marker for the phylogenetic analysis within Mylonchulus species. This agrees with the previous result obtained [5,11,35]. Tree topology using Bayesian inference shows that M. hawaiiensis stand separately, which contrasts with the result obtained by Olia et al [35].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the variation that exists may be due to the geographic location. Shokoohi et al [11] and Koohkan et al [5] indicated that the populations of Mylonchulus make a monophyletic group. The present study obtained the same result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations